Virulence of Metarhizium rileyi (Ascomycota: Clavicipitaceae) to Spodoptera cosmioides (Lepidoptera: Noctuidae) (Research, Society and Development, 2020)
This work aimed to evaluate the pathogenicity of the UFMS 03 strain of Metarhizium rileyi to the Spodoptera cosmioides caterpillars under laboratory conditions. The experimental trial consisted of a completely randomized design, with six treatments. Each treatment consisted of 10 repetitions, containing five S. cosmioides caterpillars, standardized in 3 mm in length. The S. cosmioides caterpillars were placed inside Petri dishes and sprayed with the aid of an adapted Poter Tower, at a pressure of 15 pounds / inch, using 1 mL of the concentrations 1.0×1010, 1.0×109, 1.0×108, 1.0×107 and 1.0×106 conidia mL-1. Afterwards, the plates were sealed with pvc film and placed in an air-conditioned chamber at 25±1 °C, 70±10% RH, and a 12-hour photophase. Mortality was verified 24 hours after spraying. The concentrations of the M. rileyi strain UFMS 03 proved to be efficient, with emphasis on the concentration 1.0×108 conidia mL-1 showing 98% efficiency, in less lethal time (14.11 days). These results show the strain UFMS 03 of M. rileyi as a control agent for S. cosmioides.